2014
DOI: 10.1242/jeb.101857
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mechanisms underlying individual variation in tolerance of food deprivation in juvenile European sea bass, Dicentrarchus labrax

Abstract: Although food deprivation is a major ecological pressure in fishes, there is wide individual variation in tolerance of fasting, whose mechanistic bases are poorly understood. Two thousand individually tagged juvenile European sea bass were submitted to two 'fasting/feeding' cycles each comprising 3 weeks of food deprivation followed by 3 weeks of ad libitum feeding at 25°C. Rates of mass loss during the two fasting periods were averaged for each individual to calculate a population mean. Extreme fasting tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 53 publications
2
24
1
Order By: Relevance
“…More recently, McKenzie et al (2014), working on fish exhibiting the same phenotype as those of Dupont-Prinet et al (2010), revealed that the difference in fasting tolerance did not depend on the routine energy expenditure during fasting; rather, it relied on a lower use of proteins as metabolic fuel, particularly during fasting. Vanderplancke et al (2015b) showed that in sea bass juveniles that experienced the same moderate hypoxia at the larval stage as in the present experiment, the growth reduction was not due to a lower feed ingestion, and was associated with a metabolic depression.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, McKenzie et al (2014), working on fish exhibiting the same phenotype as those of Dupont-Prinet et al (2010), revealed that the difference in fasting tolerance did not depend on the routine energy expenditure during fasting; rather, it relied on a lower use of proteins as metabolic fuel, particularly during fasting. Vanderplancke et al (2015b) showed that in sea bass juveniles that experienced the same moderate hypoxia at the larval stage as in the present experiment, the growth reduction was not due to a lower feed ingestion, and was associated with a metabolic depression.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, inter-strain differences only appeared during the second session, when the fish were older, with FD+ fish first passing into the normoxic tank at a higher oxygen level during the second session than during the first session, in contrast with FD-fish, which behaved similarly during both sessions. Because FD+ fish are less tolerant to feed deprivation, they may be more affected by the unpredictability of food supply, leading to an energetic trade off, herein a faster escape of low oxygen conditions (leading to an higher risk taking behavior), although the RMR of these strains are similar (McKenzie et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The fasting period allowed the fish, particularly at 5° C, to be post‐prandial. Three weeks of fasting at the higher temperatures should not cause physiological impairment (Killen et al ., ; McKenzie et al ., ) and while routine metabolic rate can be affected by fasting period, SMR remains constant after digestion has ended, regardless of temperature (Beamish, ). trueM˙O 2 was measured in trials lasting c .…”
Section: Methodsmentioning
confidence: 99%